Efektivitas Penggunaan Kartu Menuju Sehat Lansia di Posyandu Lansia Wilayah Kerja Puskesmas Cepiring Kabupaten Kendal - Sylvia Anjani (VISIKES: Jurnal Kesehatan Masyarakat, 2017)
The health services for Elderly-Integrated Health Post (IHP) include physical and emotional mental health checks that are recorded and monitored with Elderly-Growth Chart. This study aims to know the efectiveness of the use of Elderly-Growth Chart.This was qualitative research. Data collected by in-depth interviews, used interview guidelines, to the elderly-Growth Chart users, the main informants were elderly IHP health workers and triangulation informant were elderly ad elderly families.The results showed that the use of elderly-Growth Chart was not efective because since 2013 elderly-Growth Chart had not been used anymore because Elderly-Growth Chart were often lost and not taken during the elderly-IHP, tables in forms that were too small that cause diiculty to write and read and there was an additional workload on health workers to do the recording, because there were 3 reports that must be made.The recomendation is developing the recording system of health examination result of elderly IHP to help health workers, elderly and elderly families to monitor, and do early detection diseases and improve the elderly healthKeywords: elderly, elderly IHP, elderly growth chart